2020
DOI: 10.1155/2020/2424802
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum Interleukin 6, Tumor Necrosis Factor-Alpha, and Interferon-Gamma Levels in Relation to Body Mass Index and Blood Pressure in HIV Seropositive Pregnant Women Coinfected with Malaria

Abstract: Malaria and HIV are leading causes of morbidity and mortality, particularly in sub-Saharan Africa. Both diseases are highly endemic and have a wide geographic overlap with severe impact on pregnancy. This was a case-control study designed to evaluate the levels of interleukin -6 (IL-6), tumor necrosis factor-alpha (TNF-α), and interferon-gamma (IFN-γ) and their relationship with some anthropometric indices such as body mass index (BMI) and blood pressure in HIV-malaria coinfected women attending antenatal clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…44 This is further worsened by co-morbidity with HIV infection causing disease progression and severity. 45 A more longitudinal study is needed to explain the consequences of these variations in blood pressure in HIV-infected individuals especially in endemic regions of co-infections.…”
Section: Discussionmentioning
confidence: 99%
“…44 This is further worsened by co-morbidity with HIV infection causing disease progression and severity. 45 A more longitudinal study is needed to explain the consequences of these variations in blood pressure in HIV-infected individuals especially in endemic regions of co-infections.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of their malaria status, HIV-infected women's IVBMCs generate considerably lower amounts of IFN-γ than HIV-uninfected women, particularly in response to stimulation with crude blood-stage malaria antigens [74]. Other studies showed that IL-12, which contributes to IFN-γ regulation, was impaired to almost undetectable levels in IVBMC among HIV-infected pregnant women [73,78]. However, some studies have shown an increased level of IL-10 amongst HIV-infected pregnant women and a low likelihood of flora infection [79].…”
Section: Hiv Effect On the Cellular Immune Response To Malariamentioning
confidence: 99%